2001
DOI: 10.1046/j.1523-536x.2001.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Women's Preferences for Intrapartum Care

Abstract: The discrete choice experiment appears to be a useful tool in assessing the strength of women's preferences for different aspects of maternity care. Future research should include a qualitative approach to explore in greater depth the processes involved in shaping women's preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 20 publications
(28 reference statements)
3
85
0
1
Order By: Relevance
“…Thus, the results of our empirical comparisons of the three design strategies and the associated models suggest that researchers should exercise caution when considering the two other non-LMA design strategies. This suggests that the relatively common design strategy in the health economics literature of selecting an orthogonal fraction of the full factorial, and then randomly assigning the alternatives to choice sets may be problematic [2,5,8,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the results of our empirical comparisons of the three design strategies and the associated models suggest that researchers should exercise caution when considering the two other non-LMA design strategies. This suggests that the relatively common design strategy in the health economics literature of selecting an orthogonal fraction of the full factorial, and then randomly assigning the alternatives to choice sets may be problematic [2,5,8,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In our discretechoice experiment, the commodity obstetric care was presented to the respondents in form of alternative profiles that contained combinations of attributes of obstetric care (see Table 1 and Appendix A). Attributes and attribute levels that appeared important to pregnant women in previous research [26,27], and were also relevant to the Dutch context, were included in the analysis. We kept the number of attributes and their levels at a minimum to assure the feasibility of data collection.…”
Section: Preparation Of the Discrete-choice Experimentsmentioning
confidence: 99%
“…There are also problems related to self-selection and generalisation when actual behaviour is analysed [25]. Therefore, following the methodological recommendations in recent publications reporting similar analysis in other countries [26,27], we apply the method of discretechoice experiment. The discrete-choice experiment is a stated preference technique that relies on respondents' choices between hypothetical profiles to infer information about individual preferences and decision-making [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The women in this study felt that they had some choice in the mode of delivery although they were all aware that medical and midwifery opinion supported VBAC, which may have influenced their decisions (Hundley et al 2001). The reasons they gave for wanting a vaginal birth ranged from the desire to experience normal birth, the expectation of increased bonding and easier breastfeeding, reduced pain and length of recovery and the ability to take on family responsibilities quickly, especially the care of their older children.…”
Section: Discussionmentioning
confidence: 89%
“…Women require a clear reminder of why a caesarean was performed and need to be provided with evidence-based information regarding the chances of a recurrence of the problem, which resulted in an operative delivery (Bainbridge 2002). Clinicians, both midwives and obstetricians, must ensure that current evidence informs their thinking as it is clear that women are easily influenced by professional beliefs (Hundley et al 2001). This is especially significant when it can be demonstrated that beliefs widely held by professionals are not always substantiated by the best available research.…”
Section: Discussionmentioning
confidence: 99%